Novel cork-polymer composites reinforced with short natural coconut fibres : effect of fibre loading and coupling agent addition - Fernandes, E. M. (2013)
Composites from high density polyethylene filled with cork powder and coconut short fibres, in two different ratios, were prepared in a twin-screw extruder followed by compression moulding process. The main motivation of this work was to improve the mechanical performance without compromising the use of high weight percentage of natural component used in the preparation of cork-based composites. The morphology of the hybrid composites were more homogeneous in the presence of the coupling agent (CA) displaying enhanced fibre–matrix adhesion. Moreover, the use of CA based on maleic anhydride promotes a mechanical reinforcement effect on the tensile properties, including the elongation at break. The addition of coconut fibre resulted on an increase of 27% in elastic modulus and 47% in the tensile strength when compared with the unreinforced cork-based (50–50) wt.% composite. This work clearly shows that the addition of 10 wt.% of short-coconut fibres, randomly distributed, can be effectively used as reinforcing strategy of cork-based composite materials, preferably in the presence of 2 wt.% of CA.